2017
DOI: 10.1080/07420528.2016.1267187
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural validity of Morningness-Eveningness Stability Scale improved (MESSi) in Iran, Spain and Germany

Abstract: Morningness-Eveningness Stability Scale improved (MESSi) is a newly constructed measure to assess circadian types and amplitude. In this study, we applied this measure to participants from three different countries: Germany, Spain and Iran. Confirmatory factorial analysis (CFA) of MESSi displayed mediocre fit in the three countries. Comparing increasingly stringent models using multigroup confirmatory factor analyses indicated at least partial measurement invariance (metric invariance) by country for Morning A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 32 publications
3
24
0
Order By: Relevance
“…Higher MA or EV scores represent higher morning and evening orientation, respectively, while higher DI values indicate higher daytime fluctuations. MESSi's factorial invariance, structure, and reliability have already been confirmed repeatedly in different languages [18,[20][21][22][23]. In addition, actigraphy data corroborated the validity of the MESSi [24].…”
Section: Chronotypesupporting
confidence: 56%
“…Higher MA or EV scores represent higher morning and evening orientation, respectively, while higher DI values indicate higher daytime fluctuations. MESSi's factorial invariance, structure, and reliability have already been confirmed repeatedly in different languages [18,[20][21][22][23]. In addition, actigraphy data corroborated the validity of the MESSi [24].…”
Section: Chronotypesupporting
confidence: 56%
“…Each subscale is composed of 5 items with a Likert response format coded from 1 to 5. MESSi's factorial structure and reliability Rodrigues et al, 2018;Tomazic & Randler, 2018) and its transcultural validity (factorial invariance) in Iran, Germany, and Spain (Rahafar, Randler, Díaz-Morales, Kasaeian, & Heidari, 2017) have been corroborated in four previous studies. The Cronbach's a of the scales in the current study was .872 for MA, .846 for EV, and .751 for DI.…”
Section: M/e and Chronotypementioning
confidence: 56%
“…These validation studies showed at least satisfactory internal consistency values (Cronbach’ alphas varying between 0.73 and 0.87 for Morning Affect, 0.80 and 0.84 for Eveningness, and 0.69 and 0.77 for Distinctness). Rahafar et al (2017) further found the MESSi to be invariant at the configuration level only across the three countries involved in their study (Germany, Spain. and Iran); in other words, the three-factor model fitted acceptably for each country but the loadings and intercepts of items (particularly for the Eveningness measure) seem to differ across countries.…”
Section: Introductionmentioning
confidence: 85%
“…The MESSi has been submitted to several validation studies, namely in Germany, Spain, Iran, Portugal, and Slovenia (Randler et al, 2016a; Díaz-Morales and Randler, 2017; Diaz-Morales et al, 2017; Rahafar et al, 2017; Rodrigues et al, 2018; Tomažič and Randler, 2019). In short, all studies have replicated the three-factor internal structure (i.e., Morning Affect, Eveningness, and Distinctness) via exploratory (Randler et al, 2016a) or confirmatory factor analyses (Díaz-Morales and Randler, 2017; Diaz-Morales et al, 2017; Rahafar et al, 2017; Rodrigues et al, 2018). However, the factor structure has not been challenged by comparing a one-, two- or three-factor structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation